CUSTOMIZED AI-POWERED SECURITY AND PRIVACY CONFIGURATIONS FOR SOCIAL MEDIA WEBSITES. - Ehsan Abbas; Anis Ahmed Qazi (CV. Multi Kreasi Media, 2024)
The revolutionary field of Personalized AI-Backed Privacy and Security Settings for Social Media Web Applications is examined in-depth in this review study. The introduction lays the groundwork by outlining the escalating worries about security and privacy in the digital era, which prompts an investigation into AI-driven solutions customized to meet the demands of specific users. The background explains past struggles and the shortcomings of conventional privacy settings, laying the groundwork for the development of customized AI solutions. After that, the essay explores the necessity of customization in security and privacy settings, highlighting the variety of user preferences, the dynamic nature of threats, and the fine line that must be drawn between user experience and privacy. It presents the emergence of personalized AI solutions, propelled by sophisticated machine learning algorithms that assess user behavior in real-time and dynamically adjust security and privacy settings. This overview of privacy and security settings looks at the standard capabilities and accompanying restrictions provided by social media sites. In the part on practical implementation, case studies from well-known social media platforms are highlighted with an emphasis on best practices, lessons learned, and successful implementations. The benefits and advantages section describes how adaptive security measures, better privacy protection, and an improved user experience are all brought about by personalized AI solutions. Discussions about possible cost savings and operational efficiency arise when platforms adopt automation and AI-driven personalization.